2011
DOI: 10.1371/journal.pone.0028610
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Chinese Version of the Perceived Stress Scale in Policewomen

Abstract: BackgroundThe 10-item Perceived Stress Scale (PSS-10) is one of most widely used instruments to measure a global level of perceived stress in a range of clinical and research settings. This study was conducted to examine the psychometric properties of the Simplified Chinese version of the PSS-10 in policewomen.MethodologyA total of 240 policewomen were recruited in this study. The Simplified Chinese versions of the PSS-10, the Beck Depression Inventory Revised (BDI-II), and the Beck Anxiety Inventory (BAI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
166
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 21 publications
23
166
1
1
Order By: Relevance
“…Quando analisadas as pontuações médias da PSS por sexo, em suas três versões, o achado foi consistente com outros estudos (Cohen & Janicki-Deverts, 2012;Kajantie, 2008;Lavoie & Douglas, 2012;Wang et al, 2011), em que as mulheres tendem a exibir maior média e, em particular, no fator negativo das escalas. Quanto às demais variáveis sociodemográfi cas, a PSS-14 mostrou maior capacidade discriminativa, pois todas denotaram signifi cância estatística na comparação entre estratos, o que concorda com outras investigações (faixa etária, Hur, MacGregor, Cherkas, Williams, & Spector, 2012; escolaridade, faixa de renda e ocupação, Abbott, 2007; tabagismo, Leung et al, 2010).…”
Section: Discussionunclassified
“…Quando analisadas as pontuações médias da PSS por sexo, em suas três versões, o achado foi consistente com outros estudos (Cohen & Janicki-Deverts, 2012;Kajantie, 2008;Lavoie & Douglas, 2012;Wang et al, 2011), em que as mulheres tendem a exibir maior média e, em particular, no fator negativo das escalas. Quanto às demais variáveis sociodemográfi cas, a PSS-14 mostrou maior capacidade discriminativa, pois todas denotaram signifi cância estatística na comparação entre estratos, o que concorda com outras investigações (faixa etária, Hur, MacGregor, Cherkas, Williams, & Spector, 2012; escolaridade, faixa de renda e ocupação, Abbott, 2007; tabagismo, Leung et al, 2010).…”
Section: Discussionunclassified
“…The PSS has been demonstrated to be a reliable and valid instrument (Roberti, Harrington, & Storch, 2006), and its good reliability and validity has also been shown in many studies with different Chinese sample populations (Wang et al, 2011;Yu & Ho, 2010). The State-Trait Anxiety Inventory (Spielberger, 1983), which is one of the most universal scales used to measure anxiety (Gotlib & Cane, 1989), was also administered.…”
Section: Questionnairesmentioning
confidence: 99%
“…The perceived stress scale has been shown to correlate with stressful life-event scores (Cohen et al 1983), stress hormone levels (Pruessner et al 1999) and levels of immune markers (Glaser et al 1999). The Chinese version of the PSS-10 has demonstrated high reliability with reported coefficients ranging from .77 to .86 (Wang et al 2011). However, past studies on Asian samples have indicated poor reliability for some items (Wongpakaran and Wongpakaran 2010;Leung et al 2010) including the present young sample (Teh et al 2013).…”
Section: Perceived Stress Scalementioning
confidence: 99%